Exploring the Power of Pranic Healing: An Evidence-based Perspective on Daivavyapashraya Chikitsa - Vinushree M K S; Venkatakrishna K V (RGUHS Journal of AYUSH Sciences)
Utilization of divine or subtle energies to treat disease constitutes Daivavyapashraya Chikitsa DC. Mantra Manidharana Dana Tapa Niyama etc. show effect through Prabhava. DC is the first among Trividha Chikitsa that offers multiple possibilities for utilizing the energy.nbsp Prana is the first Eshana Pradhana Vata a life force one responsible for physical psychological and spiritual health. Prana is universal and traditional practices like Tai Chi Chi-kung Acupuncture Marma therapy Reiki and Pranic Healing use Prana for therapeutic purposes. Pranic Healing PH is a science that uses Prana to balance the energy conditions of the body for restoring physical and psychological health. The healer removes the diseased energies and transfers fresh Prana to an affected part. PH acts on Pranamaya Manomaya and other subtle Koshas. This is a perfect example of DC. A comprehensive literary review was done using classical texts online and offline scientific journals in PubMed Scopus etc. to search for evidence on DC. Research papers on Prana Pranic perception effect of PH were collected and analyzed. Multiple studies prove that Pranic energy can be perceived easily which induces a sense of peace. PH produced positive change in subjects with chronic obstructive pulmonary disease COPD mild to moderate depression and fibromyalgia. It improves the quality of life. PH has the potential to be used as an adjuvant therapy with Ayurveda. Since PH and DC share similar fundamental principles this will be a perfect example of the fusion of science with spirituality.